Photoinduced Electron Transfer in a Radical SAM Enzyme Generates an S-Adenosylmethionine Derived Methyl Radical - Yang, Hao (J Am Chem Soc, 2019)
Radical SAM (RS) enzymes use S-adenosyl-l-methionine (SAM) and a [4Fe–4S] cluster to initiate a broad spectrum of radical transformations throughout all kingdoms of life. We report here that low-temperature photoinduced electron transfer from the [4Fe–4S](1+) cluster to bound SAM in the active site of the hydrogenase maturase RS enzyme, HydG, results in specific homolytic cleavage of the S–CH(3) bond of SAM, rather than the S–C5′ bond as in the enzyme-catalyzed (thermal) HydG reaction. This result is in stark contrast to a recent report in which photoinduced ET in the RS enzyme pyruvate formate-lyase activating enzyme cleaved the S–C5′ bond to generate a 5′-deoxyadenosyl radical, and provides the first direct evidence for homolytic S–CH(3) bond cleavage in a RS enzyme. Photoinduced ET in HydG generates a trapped (•)CH(3) radical, as well as a small population of an organometallic species with an Fe–CH(3) bond, denoted Ω(M). The (•)CH(3) radical is surprisingly found to exhibit rotational diffusion in the HydG active site at temperatures as low as 40 K, and is rapidly quenched: whereas 5′-dAdo(•) is stable indefinitely at 77 K, (•)CH(3) quenches with a half-time of ~2 min at this temperature. The rapid quenching and rotational/translational freedom of (•)CH(3) shows that enzymes would be unable to harness this radical as a regio- and stereospecific H atom abstractor during catalysis, in contrast to the exquisite control achieved with the enzymatically generated 5′-dAdo(•).